1970
DOI: 10.2136/sssaj1970.03615995003400020029x
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Taxonomy of Soils from Nine Orders by Cluster and Centroid‐Component Analyses

Abstract: Multivariate statistical procedures of numerical taxonomy were used to investigate the patterns of similarities among 59 soils. Twenty‐one morphological and laboratory characteristics of modal soil profiles from nine orders of the new classification system were used. Characters were selected to avoid high intercorrelations. Raw character values were transformed to give each character a mean of zero and variance of unity. Centroidcomponent analysis with projections of soils onto centroidcharacter axes was emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1975
1975
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Previous studies where multivariate analysis was applied to pedological and ethnopedological data treated the "individuals" as soil profiles (Cipra et al, 1970;Queiroz & Norton, 1992;Vaselli et al, 1997), topsoil layers (Williams & Ortiz-Solorio, 1981) or treatments applied on soils such as farming systems (Quiroga et al, 1998;Silva et al, 2001), among others. However, in this particular case, the "individuals" analyzed and compared were sections (horizons and layers) found in the profiles of some soils (Alfisols) that have been used for multi-crop farming and earthenware production.…”
Section: Multivariate Statistical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies where multivariate analysis was applied to pedological and ethnopedological data treated the "individuals" as soil profiles (Cipra et al, 1970;Queiroz & Norton, 1992;Vaselli et al, 1997), topsoil layers (Williams & Ortiz-Solorio, 1981) or treatments applied on soils such as farming systems (Quiroga et al, 1998;Silva et al, 2001), among others. However, in this particular case, the "individuals" analyzed and compared were sections (horizons and layers) found in the profiles of some soils (Alfisols) that have been used for multi-crop farming and earthenware production.…”
Section: Multivariate Statistical Analysismentioning
confidence: 99%
“…Ethnopedological studies attempt to support this pursue since they may provide more in-depth understanding of the relationship among humans, soils and other constituents of the ecosystems . The rationale is that social groups tend to assign different meanings to soils (Brady, 1989;Krasilnikov & Tabor, 2003;Cooper et al, 2005), and that decisions and practical attitudes of use and management adopted by these groups are based on their specific knowledge and cosmovision. These are generally transmitted through generations without necessarily using written language (Toledo, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Supplementary charts of redder Hues, 7.5R and 5R are available; consequently other authors have used similar scales starting at different Hues (e.g. Russell & Moore, 1976;Cipra et al, 1970;Campbell et al, 1970;Norris & Dale, 1971;Webster & Butler, 1976) or have extended the scale to include the gley colours also (Cuanalo & Webster, 1970;Muir et al, 1970). It is implicit in these scales that differences of one unit of Hue, one unit of Value and one unit of Chroma are all perceptually equal and that the co-ordinates of these scales are mutually orthogonal.…”
Section: O M P a R I S O N O F S O M E M O D E L S F O R D E P I C mentioning
confidence: 99%
“…to examine the interrelationships of 23 Glamorganshire profiles, producing results similar to those of the soil surveyor. Cipra et al (1970) used the coordinate method to represent the similarity of soils rather than use a classification technique, the latter necessitating assumptions that clusters already exist and can be distinguished. Anderson ( t g7 i ), in discussing multivariate analysis of soil samples, suggested that the requirement of orthogonal projections, basic to many ordination solutions, places an arbitrary restraint on the solution.…”
Section: Correlations Between Soil Propertiesmentioning
confidence: 99%